STRATEGI PENGGUNAAN MEDIA VIDEO DALAM PEMBELAJARAN BAHASA INDONESIA UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK SISWA SD - Dewa Ayu Ambarawati; I Komang Eka Putra; I W Heru Sanjaya; Ni Made Prila Trisna Rini; Ni Putu Diantari; Ida Bagus Putrayasa; I Nyoman Sudiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the effectiveness of integrating video media into Indonesian language instruction to enhance the listening skills of elementary school students. Employing a classroom action research methodology, the study was conducted over two cycles with fourth-grade students at SD 12 Dauh puri. Each cycle encompassed planning, implementation, observation, and reflection phases. Data collection methods included listening comprehension tests, classroom observations, and student interviews. The findings revealed a significant improvement in students' listening abilities, with the percentage of students achieving the minimum mastery criteria increasing from 70% in the first cycle to 90% in the second cycle. Additionally, students exhibited heightened engagement and enthusiasm during lessons incorporating video media. These results suggest that the strategic use of video media is an effective approach to bolster listening skills in Indonesian language learning at the elementary level.